INOVASI KAMUS DIGITAL TERMINOLOGI MEDIS SISTEM MUSKULOSKELETAL (MusTerm) UNTUK PENUNJANG PEMBELAJARAN MAHASISWA - Syifana Putri, Riska; Shila Rochmana, Ukhta; Sari Mulina, Atika; Fauzi Ardiansyah , Muhammad; Ikhwan, Sabil; Tomy Abiyasa, Maulana; Agiwahyuanto, Faik (VISIKES, 2024)
The implementation of coding requires information recorded on the form including the writing of medical terminology. In the medical field, understanding medical terms is very important, because in the medical world there are many terms that are difficult to understand. The use of the internet is characterized by the development of web-based systems. The delivery of information with the website only takes a short time and can be done anywhere. Whereas currently the learning method has not used a system or application so that students find it difficult to understand and remember medical terms. The design of a website-based dictionary of medical terms aims to facilitate the learning of medical terms for students. The service is made using a Research and Development (R&D) research design with the Rapid Application Development model. PHP programming language with the help of sublime text. The result of this PKM is a digital dictionary website for medical terminology of the musculoskeletal system which consists of three stages, namely needs analysis, design, and implementation. The data in this study were collected by interviews, literature studies, and questionnaires. The digital dictionary website of medical terminology of musculoskeletal system can be implemented and used for learning media in DIII Medical Records and Health Information Study Program, Faculty of Health, Dian Nuswantoro University (Udinus).